REFORMASI PAJAK DAN PENINGKATAN KEPATUHAN UMKM: STUDI LITERATUR ATAS IMPLEMENTASI TARIF PPH FINAL DAN SIMPLIFIKASI ADMINISTRASI - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the effectiveness of tax reforms, particularly the implementation of a 0.5% final income tax rate and administrative simplification policies, in improving tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The method used is a literature review, analysing various secondary sources, including scientific journals, government reports, and relevant regulations. The findings indicate that the reduction in tax rates and administrative simplification have a positive impact on MSME tax compliance, expand the tax base, and improve business liquidity and competitiveness. However, the effectiveness of these policies still faces challenges such as low tax literacy, limited access to information, and the potential for double taxation due to administrative inconsistencies. This study recommends the need for continuous education, regulatory improvements, and collaboration between the government and MSME stakeholders to create a more inclusive and equitable tax system. These findings are expected to serve as a foundation for the formulation of more effective tax policies that support the sustainable growth of SMEs.